MENANAMKAN KARAKTER BANGSA MELALUI LAGU-LAGU PATRIOTIK BAGI PESERTA DIDIK TINGKAT PENDIDIKAN DASAR - Muliati, Binti; Sari, Rismalia (Jurnal al Hikmah, 2018)
The era of globalization has begun to feel with no bulkhead between people, between regions and even between countries. If there is no identity embedded in a recognizable person or nation, it will be difficult to recognize one nation with another, and then the sovereignty of the state must be easily shaken. For that it is necessary to prepare a generation of tough, who have the character, moral integrity, high morale to defend it. One of these efforts can be instilled through patriotic songs, national and nationalism, of which the songs are expected to form the soul of patriots, officers, knights, tough, and cultivate good behavior and healthy personality early on. This article tries to elaborate on the importance of state identity cultivation through patriotic songs, such as a song recently loomed by the younger generation of NU, the song SyubbanulWathan, a song that is thought to evoke a sense of patriotism, which the expected results of this idea is (1) to re-awaken all parties to the importance of national songs, struggles and patriotics among the community, especially the students, to revive semnagatpatritisme and the formation of a strong nation character (2) to formulate ways to utilize national songs and the struggle is to cultivate the spirit of patriotism and the formation of the character of the nation, so that the value of the fight and spirit of idealism aspired to the heroes of the past can be strongly rooted among young people, especially the age of SD / MI, (3) to understand the younger generations will be valuable national songs and struggle, as the legacy of the warrior ter (4) cultivate a love for the art of music that can refine mind and feeling, or to form a good character, (5) to overcome various deviations of behavior and personality bad or negative in the younger generation through songs and music